An Investigation of Urban Chinese Consumers’ Perception and Response to Corporate Social Responsibility (CSR) - Wang, Zhijian (2011)
The purpose of this research is to draw a general picture to the questions: how Chinese consumers understand and perceive “Corporate Social Responsibility (CSR)”, and how they respond to issues related to CSR. The framework of research is built on theories and concepts of CSR that are mainly developed in western developed societies. The empirical research was conducted in form of questionnaire-based survey. This research finds: Chinese consumers, although have limited understanding of the term “Corporate Social Responsibility”, care about social responsibility of business organisations. However, the “CSR” understood by Chinese consumers are closer to the concept of “business ethics”, rather than of the “CSR” defined by academics. Chinese consumers emphasise more on compulsory and ethical issues rather than firm’s voluntary activities. They pay greatest attention to CSR issues that may threats them in direct ways, followed by issues in related to environmental protection and treatment to employees. Many Chinese consumers believe that abiding by laws and regulations is the basic and fundamental requirement for business organisations. Finally, in terms of response, it is found that Chinese consumers are active in responding to CSR issues, but in moderate ways, they avoid radical response.